The Effect of Playing Collage Therapy in Increasing Motor Skills Development in Preschool Children - Ferasinta Ferasinta; Nurhayati Nurhayati; Lussyefrida Yanti (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: The stages process development of each child is the same, which is the result of the maturationprocess.Aims: The aim of this study was to compare the effectiveness of playing collage therapy in improving motor skillsdevelopment in preschool children.Material and Methods: This research was a quasi-experimental study using a pre-test and post-test researchdesign. Playing collage therapy intervention was given to the 15 respondents, which has been chosen by using apurposive sampling technique.Results: The results of this study indicate that most of the children experienced motor skills development beyondexpectation (43.8%) before being given playing collage therapy. Then their motor skills development increasingas very well developed (100%) after being given playing collage therapy. Furthermore, the results of the t-testcalculation obtained a p-value of 0.000 (α 0.05), which is means that there is a significant increase in motor skillsdevelopment through preschool children aged 3-5 years in PAUD Tunas Harapan of Bengkulu after being givenplaying collage therapy.Conclusion: From the results of this research, we conclude that playing collage therapy can be used as an alternativetherapy to improve motor skills development in pre-school children..